Tp-E interval, Tp-E/QT ratio and fragmented QRS parameters in patients with panic disorder Tp-E interval, Tp-E/QT ratio and fragmented QRS in panic disorder - Kazgan, Asli; Yildiz, Sevier; Keles, Denizhan Danaci; Keles, Fikret; Kurt, Osman (Bayrakol Medical Publisher, 2021)
Aim: In the presented research, we intended to appraise ventricular repolarization and factors of myocardial change in patients diagnosed with panic disorder(PD). Material and Methods: Fifty patients with newly diagnosed panic disorder and 50 healthy individuals as a control group were included in the research. All participants were administered Sociodemographic Data Form, Panic Disorder Severity Scale (PDSS), followed by electrocardiography (ECG). Results: Tp-e interval, Tp-e/QT ratio and Tp-e/QTc ratio were found to be remarkably higher in PD patients than in the control group (p<0,001). The incidenceof fragmented QRS in PD patients (72%) was significantly higher than the rate of fragmented QRS in the control group (36%) (p<0,001). The median PDSSscore of PD patients with fragmented QRS on their ECG was 16.0 (13.5-18.5), and the median PDSS score of those without fragmented QRS on their ECGwas 13.0 (9.0-16.0), thus there was a statistically remarkable difference between them (p=0.0.05). In PD patients, a moderately positive relationship has beenfound between PDSS scale score and Tp-e interval, Tp-e/QT ratio and Tp-e/QTc ratio, respectively (p=0.000 r=0.496) (p=0.002 r=0.436) (p=0.008 r=0.369). Discussion: The study suggests that untreated PD patients may be at high risk in terms of arrhythmic events due to abnormal ventricular conduction andmyocardial damage. Tp-e interval, Tp-e/QT ratio and fragmented QRS factors may allow evaluation of subclinical heart disease before the clinical presentation becomes apparent in PD.
Keywords: Panic Disorder; Tp-e Interval; Tp-e/QT; Tp-e/QTc; Fragmented QRS